Sistem Informasi Geografis Peta Interaktif Pariwisata Kabupaten Pati berbasis Sistem - Moh Ferdio Arifianto Saputro; Bambang Agus Herlambang; Ahmad Khoirul Anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The development of information technology, especially Geographic Information Systems (GIS), has made a significant contribution to improving tourism services in various regions. This research aims to analyze the level of user satisfaction with the GIS-based Pati Regency Tourism Interactive Map Application. The research method was carried out through collecting survey data from application users which involved respondents from various levels of society. This application is designed to provide comprehensive and up-to-date information regarding tourism destinations, facilities and travel routes in Pati Regency. Users can take advantage of interactive features to plan tourist trips more efficiently. Using questionnaires and interviews, this research evaluates user satisfaction with the user interface, information availability, data accuracy, and ease of use of the application.